(untitled) (Vietnam Journal of Community Medicine, 2025)
Purpose: To study the effects of drinking Magnesium alkaline ionized water on some blood lipid, blood sugar, and blood uric acid indices after two months of use. Methods: prospective study on 134 people in Quang Tri province, comparing blood lipid, blood sugar, and blood uric acid indices before and after two months of using Magnesium alkaline ionized water. Results: The average Glucose index decreased by 6.60 ± 17.87%, the group with Glucose index ≥ 5.6 mmol / l decreased by 22.62 ± 17.39 on average; the average Total Cholesterol index decreased by 13.74 ± 10.20%, the group with Total Cholesterol index > 5.2 mmol / l decreased by 27.33 ± 29.86% on average; The average triglyceride index decreased by 5.93 ± 33.55%, people with triglyceride index >1.88mmol/L decreased by 27.33 ± 29.86%; the average uric acid index decreased by 19.31 ± 1.19%, people with triglyceride >420 μmol/l, decreased by 17.22 ± 11.26%. Conclusions: After two months of using magnesium alkaline ionized water, the average blood lipid, blood sugar, and blood uric acid indices all had a clear downward trend.